An exploratory study of associations with spontaneous preterm birth in primigravid pregnant women with a normal cervical length. (12th December 2022) - Sarmento, Stephanno G. P.; Moron, Antonio F.; Forney, Larry J.; Hatanaka, Alan R.; Carvalho, Francisco H. C.; França, Marcelo S.; K. Hamamoto, Tatiana; Mattar, Rosiane; Linhares, Iara M.; Minis, Evelyn; Sañudo, Adriana; Sabino, Ester; et al.
Abstract: Background: Predictors of spontaneous preterm birth in primigravid women remain undetermined. Aim: We evaluated whether biomarkers in vaginal secretions and/or differences in the dominant bacterium in the vaginal microbiome predicted the risk for spontaneous preterm birth in primigravid women with a cervical length >25mm. Study design: In a prospective study, 146 second trimester pregnant women with their first conception and a cervix >25mm were enrolled. The vaginal microbiome composition was characterized by analysis of 16S ribosomal RNA gene sequences. The concentrations of d - and l -lactic acid, matrix metalloproteinase (MMP) 2, 8 and 9 and tissue inhibitor of metalloproteinase (TIMP) 1 and 2 in vaginal secretions were measured by ELISA. Cervical length was determined by vaginal ultrasonography. Pregnancy outcome data were subsequently collected. There was a spontaneous preterm birth (SPTB) in 13 women (8.9%) while in an additional 8 women (5.5%) preterm delivery was medically indicated. Lactobacillus iners was the dominant vaginal bacterium in 61.5% of women with a SPTB but only in 31.2% of those who delivered at term ( p = .0354). The vaginal concentration of TIMP-1 ( p = .0419) and L-lactic acid ( p = .0495) was higher in women with a SPTB as compared to those who delivered at term. Lactobacillus iners dominance was associated with elevated levels of TIMP-1 ( p = .0434) and TIMP-2 ( p = .0161) and lower levels of D-lactic acid ( p < .0001) compared to when L. crispatus was dominant. Conclusion: In this exploratory study of primigravid women, elevations in vaginal TIMP-1 and L- lactic acid and L. iners dominance in the vaginal microbiome are associated with an increased occurrence of SPTB.